Isolation and characterisation of probiotic lactic acid bacteria from Malaysian fermented fish products budu and bosou - Ilyanie, H. Y.; Huda-Faujan, N.; Ida Muryany, M. Y.; Zuraida, J. (Faculty of Food Science & Technology, UPM., 2024)
Indexed by WOS/SCOPUS/ERA/MYCITE